Analisis Perhitungan Harga Pokok Produksi Dalam Menentukan Harga Jual (Studi Kasus Tautan Rasa Resto & Café) - Agisna, Fika Nurpadillah; Rumiasih, N. A.; Rizqi , Muhammad Nur (CV. ITTC INDONESIA, 2024)
This study aims to understand how Tautan Rasa Resto & Café determines the cost of production, to comprehend the determination of product selling prices, and to find out whether the cost of production has played a role in setting the selling prices at Tautan Rasa Resto & Café. This research is quantitative (non-statistical) and uses primary data from interviews as well as secondary data from company documents. The analysis method used is descriptive quantitative analysis, which aims to explain the calculation of the cost of production using the full costing method and to explain the selling price using the cost plus pricing method. The results of this data analysis show that the calculation of the cost of production using the full costing method results in higher figures compared to the method currently used by Tautan Rasa Resto & Café. Similarly, the calculation of the selling price using the cost plus pricing method also results in higher figures compared to the current selling price calculations at Tautan Rasa Resto & Café. Therefore, the determination of the selling price will be influenced by the calculation of the cost of production using the full costing method because this method takes into account non-production costs. Thus, the selling price set not only includes production costs but also considers non-production costs, making it more effective and profitable.